Pertumbuhan cacing tanah Eisenia fetida sp. Pada kompos limbah fleshing - Prayitno Prayitno (Majalah Kulit, Karet, dan Plastik, 2015)
The use of earthworm as a source of income and a means for managing organic solid waste such as fleshing waste has been widely applied. The aim of this research was to find the optimum ratio between fleshing waste and cow dung in the growing medium of Eisenia fetida sp. This research was conducted by growing the E. fetida sp. earthworm in the medium containing fleshing waste mixed with cow dung. The ratio of fleshing waste and cow dung was varied at 0:100; 10:90; 20:80; 30:70; 40:60; and 50:50. In addition, 2 parts of chopped stubbles per part of every sample was added as a carbon source. The prepared media were fermented for three weeks with EM4 as a starter, followed by incubation of the earthworm for six weeks. The weight and the number of earthworm were evaluated every two weeks. The optimum growth of earthworm was achieved at the 2nd week of incubation with 185.48% and 121.10% increase of weight and number of earthworm, respectively, at 40:60 ratio of fleshing waste and cow dung in the growing medium.Keywords: earthworm, fleshing waste, incubation.ABSTRAKPenggunaan cacing tanah sebagai sumber pendapatan dan juga sarana untuk penanganan limbah padat organik seperti limbah fleshing saat ini telah banyak dilakukan. Penelitian ini bertujuan untuk mengetahui kondisi optimal perbandingan antara limbah fleshing dan kotoran sapi untuk pertumbuhan cacing tanah E. fetida sp. Penelitian dilakukan dengan menumbuhkan cacing tanah E. fetida sp. dalam media campuran limbah fleshing dan kotoran sapi dengan variasi perbandingan berturut-turut 0:100; 10:90; 20:80; 30:70; 40:60; dan 50:50 dan sebagai tambahan sumber karbon ditambahkan cacahan jerami sebanyak 2 bagian untuk setiap perlakuan. Semua media perlakuan difermentasikan selama tiga minggu dengan bantuan larutan starter EM4, dilanjutkan dengan inkubasi cacing tanah selama enam minggu. Berat serta jumlah cacing tanah dievaluasi setiap dua minggu. Pertumbuhan optimum cacing tanah dicapai pada minggu ke-2 dengan kenaikan bobot cacing tanah sebesar 185,48% dan jumlah 121,10% pada perlakuan perbandingan limbah fleshing dengan kotoran hewan 40:60.Kata kunci: cacing tanah, inkubasi, limbah fleshing.